1998
DOI: 10.1021/jm980182w
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Activities of Methylated Nordihydroguaiaretic Acids. 2. Targeting Herpes Simplex Virus Replication by the Mutation Insensitive Transcription Inhibitor Tetra-O-methyl-NDGA

Abstract: We had previously reported that tetramethyl-O-NGDA (M4N), a synthetic derivative of the naturally occurring nordihydroguaiaretic acid (NDGA), is able to inhibit HIV Tat transactivation by blocking host Sp1 protein at the Sp1 cognate binding site on the HIV LTR promoter. The present studies were undertaken to examine whether M4N is able to inhibit the replication of herpes simplex virus (HSV), another Sp1-regulated virus. The results showed that in Vero cells, M4N inhibits at micromolar levels (IC50 = 43.5 micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 24 publications
2
36
0
3
Order By: Relevance
“…This antiviral effect of NDGA is consistent with results obtained for DENV and HCV (9,10). It has to be remarked that the antiviral effects of NDGA or M 4 N also have been observed against viruses from other viral families, such as herpes simplex virus, human immunodeficiency virus, human papillomavirus, cowpox virus, and vaccinia virus (30)(31)(32)(33)(34). Regarding the mechanism behind the antiviral activity of NDGA, in the case of HCV, it was related to an inhibition of the SREBP pathway (10).…”
Section: Discussionsupporting
confidence: 88%
“…This antiviral effect of NDGA is consistent with results obtained for DENV and HCV (9,10). It has to be remarked that the antiviral effects of NDGA or M 4 N also have been observed against viruses from other viral families, such as herpes simplex virus, human immunodeficiency virus, human papillomavirus, cowpox virus, and vaccinia virus (30)(31)(32)(33)(34). Regarding the mechanism behind the antiviral activity of NDGA, in the case of HCV, it was related to an inhibition of the SREBP pathway (10).…”
Section: Discussionsupporting
confidence: 88%
“…TMP is a semi-synthetic small molecule that disrupts the interaction between Sp1 and guanine-cytosinerich motifs, thereby inhibiting Sp1 transcriptional activity. 8,[18][19][20] We have observed the inhibition of Sp1 binding to known Sp1-responsive promoters by TMP using chromatin immunoprecipitation assay, and decreased expression levels of Sp1-regulated proteins, confirming that the antitumor activity of TMP in WM occurs via selective targeting of Sp1 activity.…”
Section: Discussionsupporting
confidence: 54%
“…Our previous studies showed that M 4 N prevents Sp1 binding to its cognate binding sites in the promoter regions of Sp1-dependent genes (2,3). Given that the expression of survivin is Sp1-dependent (17,18), and our finding that M 4 N induces caspase-3 activation, we next investigated the effect of M 4 N on survivin gene expression.…”
Section: Down-regulation Of Survivin Expression By M4n Treatmentmentioning
confidence: 99%
“…We found earlier that an anti-HIV proviral transcriptional inhibitor, tetra-O-methyl nordihydroguaiaretic acid (M 4 N) (2,3), was able to cause growth arrest of a variety of transformed human and mouse cells in culture and in mice (4). As we have previously reported that 3-O-methyl-NDGA (Mal.4) inhibited HIV proviral transcription by specifically blocking Sp1 transcriptional factor to bind HIV long-terminal repeats (5), M 4 N, a DNA major groove binder for G͞C-rich sequence, was found to block cell-cycle progression at G 2 ͞M by inhibiting the transcription of an Sp1-dependent gene coding for cyclin-dependent kinase (Cdc2).…”
mentioning
confidence: 99%